Rounding Up Perspective and Its Correlation Towards Uncertainty of Measurement as an Effort to Complete Scales (Conventional Scale Case Study) Syar’i - Win Indra Gunawan (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2017)
Islam is a religion that bring salvation for mankind, teaches integrity on the trading process, where the principle of exchange is allowed for seller and buyer. Trading process that used scales usually not appropriate for buyers who want buy groceries (e.g egg and rice) because difficult to determine an accurate count values. The best estimate measurement is a randomly observed value against n repeated observations so obtained: with result , so that in conventional cases it is very difficult if the sellers do the weigher repeatedly. Islam forbids the seller to reduce the weigher, this statement is written in Al-Qur’an (Al-Mutaffifin: 1-3). Trading principles are based on an agreement between buyer and seller, so they are free to set the prices and profits. As a trader, certainly they don't want to suffer a financial loss, they need to apply shari'ah law when selling goods using scale. Islam provides a solution to the above problem as it is written in Al-Qur’an (Al-An’am: 152) and give full measure and weight in justice, to avoid reducing the weigher so not harming the buyer.